Reviweing and Analyzing Course Book of University Level: A Case Study of Arabic Grammar and Reading Text - Issa Motaghizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
University course books have a determining role in the teaching/learning process. A desirable course book has certain characteristics which differentiates it from a non-academic book. Reviewing and evaluating the content of the course book can lead to a better precision and accuracy in its design and organization. Using library research methodology in this study, an attempt has been made to obtain a framework which represents university course book characteristics. Our goal in this study was that by analyzing course book content we can also evaluate and review the definition and terminology of course book analysis, its application, dimensions, the related comments and interpretations. The book “Arabic Grammar and Reading” by Dr. Mohammad Reza Najjarian has been chosen as the case study, so we can check how well the book has benefited from the characteristics obtained. Course book is one of the most important and influential instructional medium which is very significant in the realm of education. Analyzing the content of course book can provide a better chance for the authors, course and curriculum planners and instructors to find the strengths and possible weaknesses of the books and also make revisions, and the  possible changes to the content the books based on a desirable goal and academic principles can be helpful.